2018
DOI: 10.1021/acs.energyfuels.8b00249
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Investigation of Asphaltenes-Stabilized Water-in-Oil Emulsions

Abstract: This study presents in situ visualization of the emulsification/demulsification of asphaltene-stabilized water-in-oil emulsions using microfluidic devices. Monodisperse water-in-oil emulsions were generated using a T-junction, and droplet coalescence was analyzed further upstream of the collision chamber. The state of aggregation of asphaltenes contained in the model oil was found to strongly affect the stability of the emulsions. The aqueous phases used in this study contained either surfactant (C12–15E7) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 39 publications
1
40
0
Order By: Relevance
“…8[b]; R 2 = 0.62). The general trend agrees with the widely accepted premise that precipitated asphaltene can stabilize water-in-oil dispersion, probably due to the formation of an asphaltene rigid layer at the oil/water interface and its ability to provide electrostatic and steric repulsion for a repulsive disjoining pressure [62][63][64][65] . Duboue et al 49 .…”
Section: Correlation Between Wettability Alteration and The Microdispsupporting
confidence: 88%
“…8[b]; R 2 = 0.62). The general trend agrees with the widely accepted premise that precipitated asphaltene can stabilize water-in-oil dispersion, probably due to the formation of an asphaltene rigid layer at the oil/water interface and its ability to provide electrostatic and steric repulsion for a repulsive disjoining pressure [62][63][64][65] . Duboue et al 49 .…”
Section: Correlation Between Wettability Alteration and The Microdispsupporting
confidence: 88%
“…The measurements were performed in a long serpentine channel without flow, and the coalescence times were twothree orders of magnitude longer than in the previously cited literature. Lin et al used a collision chamber to investigate coalescence of asphaltene stabilized water-in-oil emulsions in the presence of de-emulsifiers 30 , however, they focused on comparing coalescence rates, rather than coalescence times. Finally, a recent paper by Wang et al presented the effect of dissolved oxygen on coalescence kinetics of squalene droplets in water 31 .…”
Section: Introductionmentioning
confidence: 99%
“…From this point of view, it is of interest to study the composition of the interphase layer of the field WOE and the structure of its stabilizing components. According to the results of the analysis, it was found that the interphase layer of the field oil-water emulsion of the Gremikha field contains 0.34% of stabilizing components, represented mainly by asphaltenes (92.6%)the main compounds that causes the formation of highly stable oil-water emulsions [17]. Table 3 shows comparative data on the structure of resins and asphaltenes isolated from the studied oils and the structure of asphaltenes from the stabilization layer of the WOE.…”
Section: Results and Discoussionmentioning
confidence: 99%
“…At the same time, the RAS because of the presence of polar and non-polar fragments in one molecule have both hydrophilic and hydrophobic properties and exhibit high surface-active properties at the oil/water interface, which leads to the formation of stable oil-water emulsions. [4,16,17]. The stability of WOE is caused by the qualitative and quantitative composition of natural stabilizers concentrated in the interfacial layer [18][19][20].…”
Section: Introductionmentioning
confidence: 99%